Sepsis-induced acute kidney injury: kidney protection effects by antioxidants - Carolina Ferreira Vasco; Mirian Watanabe; Cassiane Dezoti da Fonseca; Maria de Fátima Fernandes Vattimo
ABSTRACT Objective: To evaluate the antioxidant action of N-acetylcysteine and diosmin-hesperidin in an experimental model of sepsis-induced acute kidney injury in rats. Methods: The study used 20 Wistar adult male rats divided into the following groups: control (laparotomy with no induction of abdominal sepsis), sepsis (experimental model of sepsis with cecal ligation and puncture), N-acetylcysteine + sepsis and diosmin-hesperidin + sepsis. The evaluation contemplated physiological parameters (temperature, glycemia, and average blood pressure), kidney function (creatinine clearance), oxidative stress (urinary peroxides) and kidney histology. Results: The animals submitted to cecal ligation and puncture (sepsis) presented lower body temperature, lower average blood pressure, reduced creatinine clearance and increased urinary hydrogen peroxide levels. Treatment with diosmin-hesperidin improved kidney function and led to a reduction in the excretion of oxidative metabolites. Conclusion: The present study highlighted the protective antioxidant action of diosmin-hesperidin in the experimental model of sepsis-induced acute kidney injury.